Evaluasi Penilaian Kinerja Guru Untuk Meningkatkan Kualitas Pembelajaran - Eka Julia Putri; Marhatul Fatwa; Nurul Anjani Daulay; M. Abdillah Khairi (Journal of Creative Student Research, 2024)
Teacher performance evaluation is essential to improving and maintaining the quality of education. Through these evaluations, teachers' strengths and weaknesses can be clearly identified, allowing for more appropriate professional development. When the quality of teachers' teaching improves, student achievement also tends to rise, showing the close relationship between teacher evaluation and student learning outcomes. The purpose of the study is to find out the various models and methods of teacher performance evaluation and the obstacles in implementation as well as strategies to improve teacher work assessment so that the quality of learning also increases. The research method used is library research. Based on the results of the research, it was found that there are various models of teacher performance evaluation and their impact on the quality of learning.